Digitalization of Business Administration in Government: Strategy towards Smart Government - Prayitno, Arief (Journal of Governance, 2025)
Digitalization of business administration in government is a strategic step in realizing a smart government that is more efficient, transparent, and responsive to the needs of the community. This study aims to analyze the role of digitalization in government business administration, identify strategies that can be applied to support the transformation towards smart government, and examine the challenges faced in the digitalization process. This study uses a qualitative approach with a descriptive method. Data was collected through in-depth interviews with government officials, technology experts, and academics, as well as through analysis of documents and policies related to government digitalization. Data analysis was carried out using the Miles & Huberman method, which includes data reduction, data presentation, and drawing conclusions, as well as using data triangulation to increase the validity of the research results. The results of the study show that digitalization of business administration in government plays a significant role in increasing the efficiency of public services, reducing complex bureaucracy, and accelerating data-based decision-making. Digitalization of government is a strategy towards a smart government that is efficient, transparent, and responsive. With digital technology, governments can improve public services, speed up administration, and support data-based decision-making. The implementation of e-budgeting, e-procurement, and e-audit strengthens modern and accountable governance. However, challenges such as the digital divide, limited internet access, high costs, low digital literacy, and data security need to be addressed through strong digital infrastructure, education, and regulations. The success of digitalization depends on the readiness of the community and apparatus, as well as the inclusiveness of services, in order to create an effective, transparent government that improves public welfare.